Children with 7q11.23 Duplication Syndrome: Psychological Characteristics - Mervis, Carolyn B. (Am J Med Genet A, 2015)
To begin to delineate the psychological characteristics associated with classic 7q11.23 duplication syndrome (duplication of the classic Williams syndrome region; hereafter classic Dup7), we tested 63 children with classic Dup7 aged 4–17 years. Sixteen toddlers aged 18–45 months with classic Dup7 and 12 adults identified by cascade testing also were assessed. For the child group, median General Conceptual Ability (similar to IQ) on the Differential Ability Scales-II was 85.0 (low average), with a range from severe disability to high average ability. Median reading and mathematics achievement standard scores were at the low average to average level, with a range from severe impairment to high average or superior ability. Adaptive behavior was considerably more limited; median Scales of Independent Behavior—Revised Broad Independence standard score was 62.0 (mild impairment), with a range from severe adaptive impairment to average adaptive ability. Anxiety disorders were common, with 50.0% of children diagnosed with Social Phobia, 29.0% with Selective Mutism, 12.9% with Separation Anxiety Disorder, and 53.2% with Specific Phobia. In addition, 35.5% were diagnosed with Attention Deficit/Hyperactivity Disorder and 24.2% with Oppositional Defiant Disorder or Disruptive Behavior Disorder-Not Otherwise Specified. 33.3% of the children screened positive for a possible Autism Spectrum Disorder and 82.3% were diagnosed with Speech Sound Disorder. We compare these findings to previously reported results for children with Williams syndrome and argue that genotype/phenotype studies involving the Williams syndrome region offer important opportunities to understand the contribution of genes in this region to common disorders affecting the general population.